Reproductive efficiency in naturally serviced and artificially inseminated beef cows - Washaya, S; Tavirimirwa, B; Dube, S; Sisito, G; Tambo, G; Ncube, S; Zhakata, X (Springer Netherlands, 2021)
A study was conducted to compare conception rates in 71 Tuli and 86 Afrikander beef cattle bred using either artificial insemination (AI) or the bull. Animals were bred using either artificial insemination or natural service at Matopos Research Station. Animals were grouped into three groups of heifers (parity 0; P0), second calvers (parity 1; P1) and mature cows (parity 2; P2) before being randomly assigned to one of the two breeding methods. A binary logistic regression was used for statistical analysis where breeding method (AI vs natural service) was the treatment factor and conception rate was the measured response while breed, parity and last calving date were non-treatment factors. No significant differences were observed in conception rates between breeds (P > 0.05). However, the method of breeding animals, parity and calving interval affected (P < 0.05) conception rates. The breeding method, parity and calving interval had a positive Kendall's tau-b correlation coefficients to conception. More animals were pregnant when AI (77.6%) was used compared with natural mating (56.79%). Conception rates were significantly lower (P < 0.05) in C1 compared with C2 cattle. The odds ratio for breeding method and parity are positive and significant (P < 0.05). In conclusion, the study confirms that artificial inseminated animals had similar conception rates to naturally serviced animals for both Tuli and Afrikander breeds. As such, artificial insemination technology can be used to complement or substitute natural service in indigenous cattle's of Zimbabwe.